Fluctuations of PM2.5 and NOx Concentration and Their Relationship with Meteorological Factors in the Rural Area (Case Study: Puncak Bogor) - Ni Putu Intan Permata Teani; Ana Turyanti; Yudith Vega Paramitadevi; Farhan Kurniawan; Ronald Christian Wattimena (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
Rural areas are generally synonymous with better air quality than urban areas. However, if there is an agricultural activity, it has the potential to release nitrogen from the soil, be oxidized and form NO and NO2 in the air. These two gases encourage the formation of secondary PM2.5 particulates in the air of rural areas. This study aims to analyze fluctuations in PM2.5 concentration in rural areas, the effect of its precursor NOx, and the influence of meteorological factors. The location used as a case study is the Cibeureum area, Puncak, Bogor Regency. The data used are PM2.5, NO, NO2, NOx concentration data (per 3 hours), rainfall, air temperature, wind speed and direction in 2019 and 2020, which were analyzed using correlation and linear regression and the open-air package provided by RStudio. The results showed that the concentration of PM2.5 with NOx as a precursor had a significant positive correlation in 2019 (r = 0.68) and 2020 (r = 0.63). Cumulative precipitation affects the concentration of PM2.5 and NOx in the air. Meteorological factors have a small correlation value to fluctuations in PM2.5 concentration and NOx concentration except for air temperature (r = 0.3).